Enhancing Cardiovascular Risk Prediction with a Simplified Carotid IMT Protocol: Evidence from the IMPROVE Study - Fabrizio Veglia; Anna Maria Malagoni; Mauro Amato; Rona J. Strawbridge; Kai Savonen; Philippe Giral; Antonio Gallo; Matteo Pirro; Bruna Gigante; Per Eriksson; Douwe J. Mulder; Beatrice Frigerio; et al. (Biomedicines)
Background/Objectives: Carotid intima-media thickness (CIMT) has long been used as an index of subclinical atherosclerosis, but its role as a risk modifier in cardiovascular (CV) risk optimization has recently been questioned due to methodological problems, such as lack of protocol standardization and scanning difficulties. In this multicentre, longitudinal, and observational study, we tested the predictive ability of two new CIMT variables detectable with a simplified, quick, and easy-to-standardize protocol. Methods: CIMT was measured in 3165 subjects from six centers, in five European countries, belonging to the IMPROVE study. The two variables tested were the average of two maximal CIMT measures taken, from a single angle, in the right and left common carotids (1CC-IMTmean-of-2-max) or bifurcations (BIF-IMTmean-of-2-max). The ability to predict CV events, on top of the SCORE2/SCORE2-OP risk algorithm, was quantified by the time-dependent increase in the receiver operating characteristic (ROC) area under the curve (AUC). Results: During a median follow-up of 7.1 years, 367 cardio-, cerebro-, and peripheral-vascular events were registered. Both CIMT variables tested were associated with CV risk, but 1CC-IMTmean-of-2-max was also able to significantly increase the ROC AUC over the risk score (+0.017, p = 0.014). The result was stable after running several sensitivity analyses. Conclusions: 1CC-IMTmean-of-2-max is able to significantly improve the predictive capacity of SCORE2/SCORE2-OP. Being based on a simple and easily standardized measurement protocol, this new variable is a promising candidate for application in mass screening and risk assessment in primary prevention.